Mechanical stability of individual bacterial cells under different osmotic pressure conditions: a nanoindentation study of Pseudomonas aeruginosa - García-Torres, Lizeth; De Alba Montero, Idania; Kolosovas-Machuca, Eleazar Samuel; Ruiz, Facundo; Bhatia, Sumati; Camacho, Jose Luis Cuellar; Ruiz-García, Jaime (Beilstein Journal of Nanotechnology, 2025)
Nanomechanical maps to test the mechanical response of the outer envelope of Pseudomonas aeruginosa were obtained utilizing atomic force microscopy in force–volume mode in the low range of loading forces when exposed to hypotonic (Milli-Q water), isotonic (PBS), and hypertonic (0.5 M NaCl) solutions. Imaging and mechanical testing showed that bacteria are highly resilient to deformation and can withstand repetitive indentations in the range of 500 pN. Analysis of force spectra revealed that although there are differences in the mechanical response within the first stages of nanoindentation, similar values in the slopes of the curves reflected a stable stiffness of about kB = 20 mN/m and turgor pressures of Pt = 12.1 kPa. Interestingly, a change in the nonlinear regime of the force curves and a gradual increase in maximal deformation by the AFM tip from hypotonic to hypertonic solutions suggest a softening of the outer envelope, which we associate with intense dehydration and membrane separation between inner and outer envelopes. Application of a contact mechanics model to account for the minute differences in mechanical behavior upon deformation provided Young’s moduli in the range of 0.7–1.1 kPa. Implications of the presented results with previously reported data in the literature are discussed.
Keywords: AFM; force spectroscopy; membrane rigidity; nanomechanical mapping; osmotic shock